Different dads : fathers' stories of parenting disabled children - Harrison, Jill, 1965-; Henderson, Matthew, 1975-; Leonard, Rob, 1969- (Jessica Kingsley Publishers, 2007)
'It is a great idea to draw together stories of fathers' experiences in bringing up disabled children. One of the ways parents manage to cope is to know that others have been through the same experiences. Then you learn that it isn't just about coping - there are positive stories to tell.'. - David Cameron MP. Fathers of disabled children can feel overlooked when the focus of much parenting support is aimed at mothers. Different Dads is a collection of inspiring personal testimonies written by fathers of children with a disability who reflect on their own experiences and offer advice to other.